2006
DOI: 10.1002/app.25376
|View full text |Cite
|
Sign up to set email alerts
|

Thermooxidative aging and kinetics of the thermooxidative degradation of ethylene–propylene–diene terpolymer‐graft‐maleic anhydride/calcium carbonate composites

Abstract: ABSTRACT:We report the preparation of five different ethylene-propylene-diene terpolymer-graft-maleic anhydride/calcium carbonate samples with different calcium carbonate contents by precipitation and their mechanical properties and structural characterization.1 In this study, we tried to analyze the thermooxidative aging and the kinetics of thermooxidative degradation with retained tensile testing for various thermal-aging times at 1508C and with hot-loading-recovery measurements. The results of the hot-loadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A variety of black and nonblack fillers of the reinforcing and nonreinforcing types cater to this need. Among several fillers, silica and carbon black are the most important reinforcing agents used in compounding recipes 1–9. Despite being well known for their strong interactions with rubbers, these fillers are relatively expensive compared with natural fillers.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of black and nonblack fillers of the reinforcing and nonreinforcing types cater to this need. Among several fillers, silica and carbon black are the most important reinforcing agents used in compounding recipes 1–9. Despite being well known for their strong interactions with rubbers, these fillers are relatively expensive compared with natural fillers.…”
Section: Introductionmentioning
confidence: 99%
“…When NR is blended with EPDM, it is often found necessary to modify it with fillers to improve the modulus, failure properties (tensile and tear strength), and abrasion resistance and reduce unit manufacturing costs while maintaining a high level of product quality and performance. Many studies on the mechanical properties of various rubber compounds have been reported, including the effect of the type and the amount of rubber and filler, and the interaction between rubbers and fillers 3–11. Filler dispersion also plays an important role in reinforcement.…”
Section: Introductionmentioning
confidence: 99%